Does the market care about investor protection practices in China?. Issue 5 (26th January 2018) - Cheung, Yan-Leung; Dang, Yin; Jiang, Ping; Lu, Tong; Tan, Weiqiang
ABSTRACT: This study develops a scorecard with which to measure the investor protection practices of major listed firms in China during 2007–2010. We use time-series data to examine the relationship between the change in firm investor protection practices and market performance. Our results show that firms exhibiting improvements in investor protection practices manifest a subsequent increase in buy-and-hold abnormal returns. The results further indicate that the changes in the sub-index have different effects on a firm's future performance. Shareholder rights to be rewarded seem to have the most significant and positive effect on a firm's future performance for both local and international investors. Moreover, international investors pay attention to their rights to information. Our results provide evidence in support of the notion that the market does care about firm's investor protection practices. The findings are robust to other measures of firm performance.